Attitudes and perceptions of marriage and divorce among Indian Muslim students - Naidoo, Suraya (Rhodes University, Faculty of Humanities, Department of Sociology, 2001)
This study explores the question of religion and ethnicity as a source of family diversity and ideology. An ideal-typical "traditional Muslim family ideology" was developed and tested. Eight Indian Muslim students at Rhodes University were asked about their attitudes and perceptions of marriage and family life, to determine the particular type of family ideology that these students embraced. Family-related issues such as marriage; the division of labour; gender roles; the extended family system; divorce; and polygamy were addressed. On the basis of the research results, it was found that these students largely adopted the "traditional Muslim family ideology". Religion and ethnicity were found to play an important role, in the make-up of these students' perception of marriage and family life, and a strong preference for the extended family was shown.
Keywords: Muslim families -- Social life and customs; Muslim students -- Attitudes